(untitled) (Research, Society and Development, 2022)
Objective: To report the experience of nursing academics in carrying out educational activities in the waiting room, in the environment of a Basic Health Unit, about uterine colon cancer. Method: This is an experience report, based on the experiences of a group of students of supervised internship I, the course of bachelor’s degree in nursing at the Regional University of Cariri, in the fields of practice focused on primary health care carried out in the interior of Ceará in the first half of 2022. The group of mediators organized the thematic in exposition in points for dialogue, being them: What is the impact of cervical cancer on the Brazilian population? What risk factors, harmful habits, and hereditary factors influence the development of diseases such as cervical cancer? Prevention and screening strategies offered by the Family Health Strategy and ways to reconcile these actions with women’s daily routine. Conclusion: the intervention resulted in important discussions that broadened the view of the group of mediators about the causes and influences that may contribute to health decisions of the population, thus contributing to the construction of a humanized, equitable and comprehensive training process for the population.